COVID crisis, austerity and the 'Left Behind' city: Exploring poverty and destitution in Stoke-on-Trent. (December 2022) - Etherington, David; Jones, Martin; Telford, Luke
Whilst the COVID-19 pandemic and 'cost of living' crisis revealed and intensified the United Kingdom's (UK) socio-spatial inequalities, these crises did not emerge into a vacuum. Long-term trends of deindustrialisation and austerity have meant many places particularly the former industrial areas across the North and Midlands have been 'left behind'. The current crises have exposed the structural fault-lines created by austerity across 2010/20 especially comprising significant cuts to welfare and local government services, with the outcome being sizable parts of the UK's post-industrial landscape experiencing poverty and destitution. In this paper, we focus upon deindustrialised Stoke-on-Trent in the North Midlands of England. Enduring long-term deindustrialisation and suffering from austerity, the article draws on qualitative and quantitative data to outline how the city contains a panoply of embedded structural problems including low-paid jobs, welfare retrenchment, poverty and destitution. Given it is a possibility that austerity will be reimposed after the next UK general election in December 2024, the paper concludes by briefly discussing the implications of these structural problems for UK government policy, indicating the urgent need for alternative policies to adequately address structural issues in places like Stoke.